The settlement of disputes in early medieval Europe / edited by Wendy Davies and Paul Fouracre. - Davies, Wendy, 1942-; Fouracre, Paul (Cambridge University Press, 1986)
This is a collection of original essays on the settlement of disputes in the early middle ages, a subject of central importance for social and political history. Case material, from the evidence of charters, is used to reveal the realities of the settlement process in the behaviour and interactions of people - instead of the prescriptive and idealised models of law-codes and edicts. The book is not therefore a technical study of charters evidence. The geographical range across Europe is unusually wide, which allows comparison across differing societies. Frankish material is inevitably prominent, but the contributors have sought to integrate Celtic, Greek, Italian and Spanish material into the mainstream of the subject. Above all, the book aims to 'demystify' the study of early medieval law, and to present a radical reappraisal of established assumptions about law and society.